Reconstruction of the Anterior Cruciate Ligament in Athletes – A Review of Methods and Treatment Outcomes - Dudek, Stanisław; Koziak, Weronika; Makieła, Michalina; Bętkowska, Aleksandra; Kornacka, Agata; Dudek, Wojciech; Szostak, Kamila; Tomaka, Rafał; Byra, Anna; Makieła, Marta (Quality in Sport, 2025)
Background: ACL injuries are common in sports requiring sudden deceleration, pivoting, and directional changes. Optimizing reconstruction and rehabilitation is crucial for knee stability, reinjury prevention, and successful return to sport. Objective: This systematic review evaluates ACL reconstruction techniques, rehabilitation protocols, and return-to-sport outcomes, focusing on graft selection, surgical advancements, rehabilitation strategies, and reinjury risk factors. Methods: A comprehensive search was conducted in PubMed, Scopus, Web of Science, and Google Scholar (2000–2025). Key factors analyzed included graft type, surgical methods, rehabilitation phases, return-to-sport timelines, and long-term complications. Results: Autografts, particularly bone-patellar tendon-bone (BPTB) and quadriceps tendon grafts, provide superior biomechanical strength and lower failure rates compared to allografts and synthetic grafts. Allografts, while suitable for lower-demand patients, have higher failure rates in young athletes. Rehabilitation plays a crucial role in recovery, with neuromuscular training and psychological readiness significantly influencing return-to-sport outcomes. Despite surgical advancements, only 55–65% of athletes regain pre-injury performance within two years. Psychological factors, including fear of reinjury, delay return and increase the risk of secondary injuries. Conclusions: While surgical and rehabilitation advancements have improved ACL reconstruction outcomes, challenges remain in optimizing return-to-sport success and reducing reinjury risks. Future research should focus on optimizing rehabilitation protocols, incorporating psychological interventions, and exploring regenerative therapies and AI-driven rehabilitation tools to enhance long-term athletic outcomes.